Information security and cryptology – ICISC 2015 : 18th International Conference, Seoul, South Korea, November 25-27, 2015, Revised selected papers /: 18th International Conference, Seoul, South Korea, November 25-27, 2015, Revised selected papers. (2016) - Unknown
No abstract available